The Effect of Digital Marketing Mix Strategy on Marketing Performance Through the Implementation of Customer Relationship Management MSME 4.0 DKI Jakarta - Alvina Mumtaza Yusuf; Miguna Astuti; Maria Bernadette Nani Ariani (Garuda Prestasi Nusantara Consulting, 2022)
There was a decline in the growth rate of DKI Jakarta's Gross Regional Domestic Product in 2020 due to the Covid-19 pandemic. GRDP is closely related to income and sales volume sold for MSME. Revenue and sales volume are dimensions of marketing performance. The purpose of this study is to examine the effect of digital marketing mix strategy and customer relationship management on marketing performance. Researchers used a quantitative approach by distributing questionnaires to 231 owners or managers of MSME 4.0 in DKI Jakarta. The proposed research model was tested using the Structural Equation Modeling (SEM) method with the Partial Least Square (PLS) specifically using the Smart-PLS 3.3 program. The results of data analysis show that: (1) Digital Marketing Mix Strategy has a significant effect on Customer Relationship Management MSME 4.0 DKI Jakarta (2) Customer Relationship Management has a significant effect on Marketing Performance of MSME 4.0 DKI Jakarta (3) Digital Marketing Mix Strategy has a significant effect on Marketing Performance MSME 4.0 DKI Jakarta. Keywords: MSME 4.0, Marketing Performance, Digital Marketing Mix Strategy, and Customer Relationship Management.